HUBUNGAN PERTAMBAHAN BERAT BADAN IBU SELAMA HAMIL DENGAN KEJADIAN BAYI BERAT LAHIR RENDAH DI PUSKESMAS HUTA RAKYAT KEC.SIDIKALANG KAB. DAIRI - Sari, Nur Mala (Jurnal Penelitian Keperawatan Medik, 2025)
Abstract Maternal nutrition is crucial for the health of the fetus. Pregnant women need an additional 500 calories, but in early pregnancy, they often experience nausea, vomiting, and food aversions, which hinder the fulfillment of their energy needs. This study aims to determine the relationship between maternal weight gain and the incidence of low birth weight (LBW) at the Huta Rakyat Health Center, Sidikalang, Dairi Regency, in 2023. This study uses a quantitative approach with a cross-sectional design and involves 52 third-trimester pregnant women as samples selected by accidental sampling. The results of the study show a significant relationship between maternal weight gain and the incidence of LBW (p-value 0.000 < 0.05). It is expected that health workers, especially midwives providing ANC services, can closely monitor maternal weight gain and provide more intensive education on the importance of appropriate weight gain to prevent the occurrence of LBW.